Justice in Property Distribution: Comparing Islamic and Bilateral Inheritance Law - Huda, Miftakhul; Nasrulloh, Nasrulloh; Anam, Khoirul; Rahim, Abdul; Ahyani, Hisam (JURNAL AKTA, 2025)
This study examines the application of bilateral inheritance law in Indonesia in relation to Islamic inheritance principles and assesses justice in property distribution. Bilateral inheritance grants equal rights to all heirs regardless of gender, while Islamic law provides specific rules for fair distribution. Using a qualitative case study approach, data were collected through interviews with Islamic law experts, legal practitioners, and local community members, as well as analysis of relevant cases. The findings reveal that the application of bilateral inheritance often conflicts with Islamic justice principles, such as excluding deceased parents’ rights or favoring children from second marriages over the first. These inconsistencies reflect tension between local customs seeking equality and Islamic law requiring proportional fairness. The study recommends harmonizing customary and Islamic inheritance laws to improve justice in property distribution. This research contributes new insights into the challenges of integrating customary practices with Islamic legal principles in Indonesia’s inheritance system. The findings can support policymakers, legal practitioners, and communities in developing fairer inheritance practices that respect both traditions and Islamic jurisprudence.